Analisis Peningkatan Efektivitas Lean Production Management pada CV Kopi Banyuatis di Singaraja - Made Krisna Ary Basudewa; Pramono D Fewidarto; Nisa Zahra (Jurnal Manajemen dan Organisasi, 2022)
CV Pusaka Bali Persada Kopi Banyuatis (KB) is an industry that processes raw coffee beans into various ready-to-consume coffee products. CV KB experienced a number of problems that had an impact on decreasing competitiveness, such as; production activities not efficient, the occurrence of waste, care and maintenance of machines is less attention. This study aims to (1) identify waste problems and determine priority efforts for handling waste in the CV KB, and (2) analyze the increase in the effectiveness of lean production management in the CV KB. The method used is the analysis of AHP and TPM (5S work culture, eight pillars, and OEE). The results of the identification and analysis carried out, set priorities for handling waste defect (0,367) and over-processing (0,239). The increase in LPM is based on OEE calculations during January to March 2022, which is predicted to increase by 13,04 percent with availability values of 11,32 percent, performance 8,44 percent, and quality 1,57 percent. The prediction of the increase in OEE value that occurs when associated with the total sales obtained by the industry, can result in a prediction of an increase in sales profit of Rp1.552.662,800 for all products sold in 500 g packaging as many as 1890 pcs. CV KB can focus on improving the priority of handling waste, as well as maintaining the quality of machines and production facilities to increase the effectiveness of LPM.